Effect of conventional and experimental silanes on the adhesion of fiberglass posts to root canals: In vitro study - Marcos Cezar Pomini; Carmem Silvia Pfeifer; Ana Paula Piovezan Fugolin; Vitoria Massoneto Piccolli; Roberta Araujo de Paula Ramos; Rafael Leonardo Xediek Consani (Wolters Kluwer Medknow Publications, 2021)
Introduction: Thiourethane addition to methacrylate of resin cements improves properties of flexural strength, toughness modulus, and fracture toughness. The aim of this study was to evaluate the effect of experimental silanes based on thiourethane in the adhesion of fiberglass posts to the root canal submitted to thermal and mechanical cycling. Materials and Methods: Two oligomers were synthesized with catalytic amounts of triethylamine. Multifunctional thiol-pentaerythritol tetra-3-mercaptopropionate was combined with difunctional isocyanates - 1,6-hexanedioldiissocyante (aliphatic) or 1,3-bis (1-isocyanato-1-methylethyl) benzene (aromatic). Human dental root canals were treated with conventional and experimental silanes, establishing six experimental groups (n = 10) endodontically rehabilitated with fiberglass posts. The specimens were submitted to 1.2 x 106 mechanical cycles and 500 thermal cycles (5°C and 55°C). One slice from each root region (cervical, middle, and apical) was submitted to the push-out bond test, and the fracture pattern evaluated. Scanning electron microscopy micrographs were obtained from the marginal gaps occurred in the adhesive interfaces. Data were analyzed with two-way ANOVA followed by Tukey's test at α = 0.05 confidence level. Results: Conventional and experimental silanes improved bond strength (P < 0.001) with similar values among the root regions (P = 0.199), decreased the occurrence of adhesive failures in dentin-cement bond, and increased the cohesive failures in dentin and the mixed failures. The marginal gaps showed in scanning electron microscopy micrographs were similar, except for the Angelus conventional silane, showing greater slit. Conclusions: Conventional and experimental silanes provided greater adhesive strength, reduced dentin-cement failures, and the marginal gaps were similar, except for the control group Angelus, showing greater slit.